Dynamic Simulation Analysis of Flight Process of Bionic Aircraft. Issue 4 (June 2019) - Wang, Xinjie; Ning, Yu; Wang, Chen; Wang, Caidong
Abstract: In this paper, the beetle (Coleoptera) is taken as a bionic object. According to the characteristic of the hind wing of the beetle that can be folded, combined with the four-plate mechanism theory, a bionic flapping aircraft with four-degree-of-freedom beetle foldable wing is designed. It can realize flapping, gliding, wing folding and abduction/adduction movement with self-locking function. At the same time, the physical model of the beetle-folding four-plate wing was established. The dynamic simulation of the flight process was carried out in ADAMS. The variation of the force and torque of the flexible hinge at different flapping frequencies is analyzed. The results show that the force and torque of the hinge have nonlinear characteristics during the take-off phase, but they tend to be stable eventually. The force and torque of each hinge first decrease and then increase as the flapping frequency increases, and the time of fluctuations becomes smaller. The simulation results provide a reference for the parameter design of the flexible hinge and the control of the aircraft motion.